Kualitas Penggunaan Antibiotik pada Pasien Community-Acquired Pneumonia di Salah Satu Rumah Sakit di Bali - Meriyani, Herleeyana; Sanjaya, Dwi Arymbhi; Juanita, Rr. Asih; Siada, Nyoman Budiartha (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Community-acquired pneumonia (CAP) is an infectious disease with high morbidity and mortality rates. Antibiotics are essential therapies for bacterial CAP. The use of antibiotics is a critical point in CAP treatment. Inappropriate use of antibiotics leads to antibiotic resistance. The study aimed to evaluate the proper use of antibiotics in CAP patients and identify the relationship between the appropriate use of antibiotics and the use of single/combined antibiotics with prolonged length of stay. This study was a cross-sectional study with retrospective data collection at a general hospital in Bali. Evaluation of the proper use of antibiotics was done using the Gyssens algorithm. The relationship between the appropriate use of antibiotics and the type of antibiotic (single/combined) with the length of stay was carried out using the Chi-square test with a 95% confidence interval. There were 151 CAP patients as samples in this study consisting of 55.63% men and 44.37% women with a median age of 60 years (18-89). The appropriate use of antibiotics was 17.88%, while 82.18% of the total antibiotic use was inappropriate. The Inappropriate use of antibiotics in category IIA (incorrect dosage) is 3.97%, category IIIB (inappropriate interval) is 4.64%, category IVC (cheaper alternative antibiotics were available) is 41.72%, and category V (no indication) is 37.79%. There is no significant relationship between the appropriate use of antibiotics and prolonged LOS [p>0.05; OR: 1.132 (CI: 0.466-2.746)] however the use of antibiotics (single or in combination) significantly affects the prolonged LOS [p<0.05; OR: 0.027 (CI: 0.004-0.204)].